2, 3-Diphosphoglycerate Concentrations in Autologous Salvaged Versus Stored Red Blood Cells in Surgical Patients After Transfusion. Issue 6 (December 2016) - Scott, Andrew V.; Nagababu, Enika; Johnson, Daniel J.; Kebaish, Khaled M.; Lipsitz, Joshua A.; Dwyer, Ian M.; Zuckerberg, Gabriel S.; Barodka, Viachaslau M.; Berkowitz, Dan E.; Frank, Steven M.
Abstract : (Abstracted from Anesth Analg, 122:616–623, 2016) Red blood cells (RBCs) undergo morphological and biochemical changes in structure during storage and are at risk of storage lesions and loss of 2, 3-diphosoglycerate (2, 3-DPG). In fact, 2, 3-DPG is nearly depleted after 21 days of storage, and although the issue is controversial, it is thought that reduced 2, 3-DPG may adversely affect oxygen delivery, seen through a shift of the oxyhemoglobin dissociation curve to the left and subsequent decrease in P50 (partial pressure of oxygen at which 50% of hemoglobin is saturated with O2 ).